Application of ionic liquids for separation of propyne from propylene: solubility and selectivity studies - Jelliarko Palgunadi; Antonius Indarto; Haryo Winoto; Hoon Sik Kim (Jurnal Teknik Kimia Indonesia, 2010)
Separation or removal of propyne from propylene, generated by naptha cracking process, is one of the most important processes in petrochemical industries because ppm level of propyne contained in feed olefins can serve as catalyst poisons in the polymerization of olefins. Recently, room temperature ionic liquids (RTILs) were introduced as novel solvents for the separation of various gases and hydrocarbons. RTIL is a salt composed of unsymmetrical organic cation and organic/inorganic anion which melts at room temperature. Prior to the decision of material selection for the effective separation of propyne/propylene employing RTIL, solubility behaviors and selectivities of propyne and propylene in various RTILs were investigated. For the solubility of propyne and propylene in 1-R-3-methylimidazolium-based RTILs, solubility measurement, thermodynamic analysis, and computational calculation strongly imply that the solubility of propyne is controlled by a trade-off between a specific solute-solvent interaction (hydrogen bonding of propyne-anion) and non bonding interaction (solubility parameter). In contrast, the solubility of propylene seems to be much strongly dependent on non-bonding interaction (solubility parameter) closely related to the physical attractive forces as suggested by regular solution theory. Thus, to achieve high selectivity of propyne over propylene, a RTIL with smaller-size and stronger hydrogen bonding ability should be employed.Keywords: propyne, propylene, solubility, selectivity, ionic liquidsAbstrakPemisahan senyawa propuna dari propena, yang dihasilkan oleh proses fraksionasi nafta adalah salah satu proses yang paling penting dalam industri petrokimia. Kontaminan propuna yang terkandung dalam umpan olefin dapat menjadi racun katalis dalam proses polimerisasi olefin. Kini cairan ionik temperatur ruang (RTIL) diperkenalkan sebagai pelarut baru untuk pemisahan berbagai gas dan hidrokarbon. RTIL adalah garam yang terdiri dari kation organik dan anion organik/anorganik asimetrik yang meleleh pada suhu kamar. Pemilihan senyawa pelarut RTIL yang tepat untuk pemisahan propuna / propena akan dibahas dalam tulisan ini. Dalam proses pelarutan propuna dalam RTIL berbasis 1-R-3-metilimidazolium, pengukuran kelarutan, analisis termodinamika, dan pemodelan mengisyaratkan bahwa kelarutan propuna dikendalikan oleh kompromi antara interaksi spesifik solut-pelarut (ikatan hidrogen propuna-anion) dan interaksi tak mengikat  (parameter kelarutan). Sebaliknya, kelarutan propena sangat bergantung pada interaksi tak mengikat (parameter kelarutan) yang erat hubungannya dengan ikatan fisik seperti dipaparkan dalam teori larutan biasa (regular solution theory). Dengan demikian, untuk mencapai selektivitas tinggi terhadap propuna dibandingkan dengan propena, disarankan untuk menggunakan senyawa RTIL dengan ukuran molekul lebih kecil yang memiliki ikatan hidrogen lebih kuat.Kata Kunci: propuna, propena, kelarutan, absorpsi, cairan ionik